Incidental detection of intrauterine device in sigmoid colon and its removal with colonoscopy - Bozdag, Ahmet; Altas, Onder; Sahin, Abdurrahman; Ozkan, Zeynep (Bangladesh Journal of Medical Science, 2017)
Intrauterine device (IUD) is one of the frequently used contraceptive methods in the developing countries, due to its high efficacy, low risks and low costs. However, it may cause some important complications. One of these complications is migration of IUD to adjacent organs. The migration of IUDs to sigmoid colon is rare and it is reported as case reports. In this article, we wanted to share the colonoscopic evaluation of a 38-year-old female patient who presented with chronic abdominal pain, meanwhile the detection of IUD in the sigmoid colon and its removal with colonoscopy. Bangladesh Journal of Medical Science Vol.16(4) 2017 p.597-599